Tenofovir based regimens associated with less drug resistance in hiv-1 infected nigerians failing first-line antiretroviral therapy. (2013)
Background: In resource-limited settings, HIV-1 drug resistance testing to guide antiretroviral therapy (ART) selection is unavailable. We retrospectively conducted genotypic analysis on archived samples from Nigerian patients who received targeted viral load testing to confirm treatment failure and report their drug resistance mutation patterns. Methods: Stored plasma from 349 adult patients on non-nucleoside reverse transcriptase inhibitor (NNRTI) regimens was assayed for HIV-1 RNA viral load, and samples with more than 1000 copies/ml were sequenced in the pol gene. Analysis for resistance mutations utilized the IAS-US 2011 Drug Resistance Mutation list. Results: One hundred and seventy-five samples were genotyped; the majority of the subtypes were G (42.9%) and CRF02_AG (33.7%). Patients were on ART for a median of 27 months. 90% had the M184V/I mutation, 62% had at least one thymidine analog mutation, and 14% had the K65R mutation. 97% had an NNRTI resistance mutation and 47% had at least two etravirine-associated mutations. In multivariate analysis tenofovir-based regimens were less likely to have at least three nucleoside reverse transcriptase inhibitor (NRTI) mutations after adjusting for subtype, previous ART, CD4, and HIV viral load [P < 0.001, odds ratio (OR) 0.04]. 70% of patients on tenofovir-based regimens had at least two susceptible NRTIs to include in a second-line regimen compared with 40% on zidovudine-based regimens (P ¼ 0.04, OR ¼ 3.4). Conclusions: At recognition of treatment failure, patients on tenofovir-based first-line regimens had fewer NRTI drug-resistant mutations and more active NRTI drugs available for second-line regimens. These findings can inform strategies for ART regimen sequencing to optimize long-term HIV treatment outcomes in low-resource settings.